Analysis and optimization of a mode of industrial product processing at an electron accelerator - Nikiforov, V.I.; Pomatsalyuk, R.I.; Rogov, Yu.V.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2015)
By means of computer simulation, the factors determinating non-uniformity of the volume distribution of the absorbed dose at product processing by scanned electron beam, namely, the energy spectrum and scanning mode, product density and homogeneity of its distribution, as well as the distance between the objects moving through the irradiation zone, are studied. On the basis of the PENELOPE-2008 package, a code for calculating the dose distribution and its non-uniformity coefficient with due regard to the beam characteristics, surface density and velocity of the object, has been developed. Verification of the code was carried out by comparison of simulation results with the experimental data obtained using a reference polystyrene calorimeter RISO as well as by dose mapping in a standard phantom. Методом моделювання досліджені чинники, що визначають нерівномірність об'ємного розподілу поглинутої дози при обробці продукції скануючим пучком електронів: енергетичний спектр і форма розгортки пучка, щільність об'єкту та однорідність її розподілу, а також відстань між об'єктами, що переміщують через зону опромінювання. На основі програмної системи PENELOPE-2008 розроблений код для розрахунку розподілу дози і коефіцієнта його неоднорідності з урахуванням характеристик пучка, поверхневої щільності і швидкості переміщення об'єкту. Виконана верифікація коду шляхом порівняння результатів моделювання з експериментальними даними, отриманими за допомогою референтного калориметра з полістиролу RISO, а також методом картування дози в стандартному фантомі. Методом моделирования исследованы факторы, определяющие неравномерность объемного распределения поглощенной дозы при обработке продукции сканирующим пучком электронов: энергетический спектр и форма развертки пучка, плотность объекта и однородность ее распределения, а также расстояние между объектами, перемещаемыми через зону облучения. На основе программной системы PENELOPE-2008 разработан код для расчета распределения дозы и коэффициента его неоднородности с учетом характеристик пучка, поверхностной плотности и скорости перемещения объекта. Выполнена верификация кода путем сравнения результатов моделирования с экспериментальными данными, полученными с помощью референтного полистирольного калориметра RISO, а также методом картографирования дозы в стандартном фантоме.